EP13 Perceptions and experiences of residents and relatives of emergencies in care homes: systematic review and meta-synthesis. Issue 9 (19th August 2021) - Laparidou, Despina; Curtis, Ffion; Udayangani Jayawickrama, Withanage Iresha; Weligamage, Dedunu; Ortega, Marishona; Siriwardena, Aloysius Niroshan
Abstract : Background: Medical emergencies in care homes, both residential and nursing care homes, are common and costly, often resulting in calls to an out-of-hours general practitioner (GP) or Emergency Medical Services (EMS). Ambulance attendance frequently results in conveyance to hospital and the concomitant high costs and risks of, often prolonged, hospitalisation. Previous reviews have focussed on various stakeholder perceptions of transfer to hospital. The aim of this systematic review was to provide a comprehensive synthesis of the perceptions and experiences of care home residents and their family members, who have experienced medical emergencies in a care home setting. Methods: We searched five electronic databases, supplemented with internet searches and forward and backward citation tracking from the included studies and review articles. Data were synthesised thematically following the Thomas and Harden approach. The CASP Qualitative Checklist was used to assess the quality of the included studies of this review. Results: The search strategy identified 6, 140 citations. After removing duplicates and excluding citations based on title and abstract, and full-text screening, ten studies from four countries (Australia, Canada, UK, and US) were included in the review and meta-synthesis. All included studies were considered of acceptable quality. Through an iterative approach, we developed six analytical themes. 1. Infrastructure and process requirements in care homes to prevent and address emergencies; 2. The decision to transfer to hospital – a perfect storm; 3. Challenges of transfer and hospitalisation for older patients; 4. Good communication vital for desirable outcomes; 5. Legal, regulatory and ethical concerns; and 6. Trusting relationships enabled residents to feel safe. Conclusions: The emergency care experience for care home residents can be enhanced by ensuring resources, staff capacity and processes for high quality care. Building trusting relationships underpinned by good communication and attention to ethical practice were also identified as important factors.